Xenopus Ssbp2 is required for embryonic pronephros morphogenesis and terminal differentiation - Cervino, Ailen Soledad (2023)
The nephron, functional unit of the vertebrate kidney, is specialized in metabolic wastes excretion and body fluids osmoregulation. Given the high evolutionary conservation of gene expression and segmentation patterning between mammalian and amphibian nephrons, the Xenopus laevis pronephric kidney offers a simplified model for studying nephrogenesis. The Lhx1 transcription factor plays several roles during embryogenesis, regulating target genes expression by forming multiprotein complexes with LIM binding protein 1 (Ldb1). However, few Lhx1-Ldb1 cofactors have been identified for kidney organogenesis. By tandem- affinity purification from kidney-induced Xenopus animal caps, we identified single-stranded DNA binding protein 2 (Ssbp2) interacts with the Ldb1–Lhx1 complex. Ssbp2 is expressed in the Xenopus pronephros, and knockdown prevents normal morphogenesis and differentiation of the glomus and the convoluted renal tubules. We demonstrate a role for a member of the Ssbp family in kidney organogenesis and provide evidence of a fundamental function for the Ldb1–Lhx1-Ssbp transcriptional complexes in embryonic development.